Identification of pathway-based toxicity in the BALB/c 3T3 cell model. Issue 6 (September 2015) - Vaccari, Monica; Mascolo, Maria Grazia; Rotondo, Francesca; Morandi, Elena; Quercioli, Daniele; Perdichizzi, Stefania; Zanzi, Cristina; Serra, Stefania; Poluzzi, Vanes; Angelini, Paola; Grilli, Sandro; Colacci, Annamaria
Highlights Dose-related toxicity was evidenced in BALB/c 3T3 cells treated with PM2.5 samples. Cell toxicity depended on PM2.5 sampling season and sampling site. Gene pathways related to toxic stress response were identified in the treated cells. No foci formation was evidenced in the cell transformation assay. Gene pathways related to chronic lung diseases and cancer onset were modulated.